PENGARUH KOMPETENSI KERJA, GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI DEPUTI BIDANG PEMBUDAYAAN OLAHRAGA KEMENTERIAN PEMUDA DAN OLAHRAGA - Paiman Raharjo; Zahera Mega Utama; Muhammad Raditya Saputra (ITB AAS Indonesia Surakarta, 2023)
Reflecting on the aspect of success in achieving goals, effectiveness focuses on the level of achievement of organizational goals, and in terms of timeliness, effectiveness is the achievement of certain predetermined targets on time by using certain resources that have been allocated to carry out various activities. This research needs to determine the objectives to be achieved, namely as follows, that this research is to determine the effect of work competence (X1), leadership style (X2), and work motivation (X3) affecting the job satisfaction variable (Y) Employee Deputy for Sports Culture Ministry of Youth and Sport. This study uses explanatory and descriptive survey methods. 4. Work Competence, Leadership Style, and Work Motivation have a significant effect simultaneously or jointly on Job Satisfaction of employees of the Deputy for Sports Empowerment at the Ministry of Youth and Sports.